2018
DOI: 10.1177/1460408618783221
|View full text |Cite
|
Sign up to set email alerts
|

Major trauma in the elderly: Frailty decline and patient experience after injury

Abstract: IntroductionThe prevalence of major trauma in the elderly is increasing with ageing western societies. Frailty is now a well-recognised predictor of poor outcome after injury; however, few studies have focused on the progression of frailty and patients’ perceptions of their injuries after discharge.AimWe hypothesised that the number of elderly patients that survive major trauma is low and, of those that do, frailty post injury worsens with overall negative views about quality of life. To investigate this, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Only one study from the UK assessed frailty during follow-up period and showed that patients aged >75 years with major trauma (Injury Severity Score [ISS] >15) had significant worsening of frailty at one-year after injury compared to pre-injury (8% of the study group were frail at pre-injury phase compared to 46% at one-year post injury). 48 It also reported that 57% had positive comments on their mental health, quality of life, and functional status whereas 29% of the participants have negative comments on the same aspects at one-year following major trauma. 48 Inaba et al 49 showed a significant decline in seven of eight health domains using the 36-item Short Form survey (SF-36) at 2.8 years after trauma for trauma patients aged ≥65 years compared to non-injured residents of the same age ( Table 2 ).…”
Section: Determining Appropriate Outcome Measuresmentioning
confidence: 96%
See 1 more Smart Citation
“…Only one study from the UK assessed frailty during follow-up period and showed that patients aged >75 years with major trauma (Injury Severity Score [ISS] >15) had significant worsening of frailty at one-year after injury compared to pre-injury (8% of the study group were frail at pre-injury phase compared to 46% at one-year post injury). 48 It also reported that 57% had positive comments on their mental health, quality of life, and functional status whereas 29% of the participants have negative comments on the same aspects at one-year following major trauma. 48 Inaba et al 49 showed a significant decline in seven of eight health domains using the 36-item Short Form survey (SF-36) at 2.8 years after trauma for trauma patients aged ≥65 years compared to non-injured residents of the same age ( Table 2 ).…”
Section: Determining Appropriate Outcome Measuresmentioning
confidence: 96%
“… 48 It also reported that 57% had positive comments on their mental health, quality of life, and functional status whereas 29% of the participants have negative comments on the same aspects at one-year following major trauma. 48 Inaba et al 49 showed a significant decline in seven of eight health domains using the 36-item Short Form survey (SF-36) at 2.8 years after trauma for trauma patients aged ≥65 years compared to non-injured residents of the same age ( Table 2 ).…”
Section: Determining Appropriate Outcome Measuresmentioning
confidence: 96%
“…1 Integration of frailty models using the Golden Gate Bridge analogy. (Used with permission from the Journal of the American Geriatric Society) including mortality, morbidity, functional decline, and major adverse cardiac and cerebrovascular events (Sepehri et al 2014;Kim et al 2016) In critical care settings, frailty is common and is clearly associated with worse outcomes (Muscedere et al 2017;Koizia et al 2019).…”
Section: Prevalence and Outcomes Of Frailty In Clinical Carementioning
confidence: 99%
“…As populations age and life expectancies increase, trauma in the elderly has more than doubled within the last decade [ 1 ]. This is a common cause of death [ 2 ], with low falls being the most common mechanism of injury (MOI), followed by motor vehicle accidents (MVAs) and high falls [ 1 , 2 ]. Although there are varying definitions of low fall such as <2 meters and patient height [ 2 ], a lower definition of <0.5 meters has been proposed [ 3 5 ], in keeping with video-capture studies demonstrating that most falls in the elderly happen from the seated or standing position [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a common cause of death [ 2 ], with low falls being the most common mechanism of injury (MOI), followed by motor vehicle accidents (MVAs) and high falls [ 1 , 2 ]. Although there are varying definitions of low fall such as <2 meters and patient height [ 2 ], a lower definition of <0.5 meters has been proposed [ 3 5 ], in keeping with video-capture studies demonstrating that most falls in the elderly happen from the seated or standing position [ 3 ]. In previous studies, we found that low falls were associated with higher readmission and mortality rates compared to higher-velocity mechanisms such as MVAs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%